ASSESSMENT OF THE NASOPHARYNGEAL CARRIER RATE OF STREPTOCOCCUS PYOGENES AND STREPTOCOCCUS PNEUMONIAE AMONG APPARENTLY HEALTHY INDIVIDUALS IN ANYIGBA, KOGI STATE, NIGERIA - Makolo, Daniel; Odugbo, Moses Ode; Emmanuel, Stephen (FUDMA Journal of Sciences, 2025)
The aim of this study was to detect the carriage rate of Streptococcus pyogenes and Streptococcus pneumoniae among apparently healthy children and adults in Anyigba, Kogi State, Nigeria. Nasopharyngeal samples were aseptically collected and analyzed in accordance with standard bacteriological procedures. The target isolates were identified based on their colonial morphology and standard biochemical tests. Out of the 300 nasopharyngeal samples analyzed, 97 isolates of target bacteria were obtained, giving an overall prevalence rate of 32.3%. This consisted of Streptococcus pyogenes 49(16.3%) and Streptococcus pneumoniae 48(16.0%). Comparing the colonization rates between children and adults’ samples, a total of 22.0% isolates of target organisms were obtained from children and 10.3% from adults. The carriage rates were higher in children than adults sampled. Also, comparing the colonization rates between the male and female subjects, 16.7% isolates of Streptococcus pyogenes and Streptococcus pneumoniae were obtained from the female participants and 15.7% from the male participants. The result showed that the samples collected from the female participants yielded higher isolates of Streptococcus pyogenes and Streptococcus pneumoniae than those from male participants. This study also established that samples from public schools yielded more isolates of Streptococcus pyogenes and Streptococcus pneumoniae (38.8%) than those from the private schools (25.6%). The asymptomatic carriage of these potential pathogens poses a potential public health threat to the people, as it could lead to epidemics of respiratory tract infections (RTIs) in future. Therefore, improved personal and public hygienic practices and decongestion of overcrowded classrooms are highly recommended.